Changes in haemostasis and inflammatory markers after mRNA BNT162b2 and vector Ad26.CoV2.S SARS-CoV-2 vaccination - Ivanko, I.; Ćelap, I.; Margetić, S.; Marijančević, D.; Josipović, J.; Gaćina, P. (Thrombosis research, 2023)
Reported thromboembolic events after SARS-CoV-2 vaccinations are still raising concerns, predominantly in non-scientific population. The aim of our study was to investigate the differences between haemostasis and inflammatory markers in the subjects vaccinated with mRNA BNT162b2 and vector Ad26.CoV2.S vaccine. The study included 87 subjects vaccinated with mRNA BNT162b2 and 84 with Ad26.CoV2.S vaccine. All the laboratory parameters (TAT, F 1 + 2, IL-6, CRP, big endothelin-1, platelets, fibrinogen, D-dimers, VWF activity) were investigated for the mRNA vaccine at five (before the first dose, 7 and 14 days after the first and second vaccine dose), and three time points (before the first dose, 7 and 14 days after) for the vector vaccine, respectively. All the markers were measured by well-established laboratory methods. Our results have shown statistically higher CRP levels in the vector group 7 days after vaccination (P = 0.014). Furthermore, study has revealed statistically significant rise in D-dimers (P = 0.004) between tested time points in both vaccine groups but without clinical repercussions. Although statistically significant changes in haemostasis markers have been obtained, they remained clinically irrelevant. Thus, our study implicates that there is no plausible scientific evidence of a significant disruption in the coagulation and inflammatory processes after vaccination with BNT162b2 mRNA and Ad26.CoV2.S vector SARS-CoV-2 vaccines.